The relationship between chronological age, dental age, and salivary alkaline phosphatase in Indonesian children aged 8–14 years: A cross-sectional study. Issue 2 (August 2021) - Nelwan, Sindy Cornelia; Wahluyo, Soegeng; Khairani, Firli Cahaya; Nugraha, Ricardo Adrian; Utomo, Haryono; Tedjosasongko, Udijanto; Nowwarote, Nunthawan
Abstract: Background: Inability to predict dental age accurately has long been the Achilles heel of pediatric dentistry. Whilst dental age has an important aspect in clinical practice, saliva can be one of the most practically important diagnostic tools to estimate biological age. Aims: This study aimed to analyze a correlation between chronological age, dental age, and salivary alkaline phosphatase in Indonesian children aged 8–14 years. Methods: This study was an observational study with cross-sectional design. Twenty healthy children (10 boys and 10 girls) were selected by consecutive sampling. Chronological age was assessed by recording date of birth. Dental age was assessed by orthopantamogram following Demirjian's method. Salivary samples were collected by passive drool method and estimation of alkaline phosphatase was done by autoanalyzer. Results: Normality test was assessed using Kolmogorov-Smirnov and Shapiro-Wilk test. Statistical analyses were assessed using Spearman's rank-order correlation coefficients. Results are presented as mean ± standard deviation (SD). Mean chronological age was 10.504 ± 1.895 years, mean Demirjian's score was 91.74 ± 5.972, and mean salivary alkaline phosphatase was 291.563 ± 115.135 pg/ml. There is a very strong positive correlation between chronological age and dental age (r = +0.804; p  < 0.001). On the contrary, levels of salivary alkaline phosphatase was negatively correlated to dental age (r = −0.780; p  < 0.001) and chronological age (r = −0.508; p  = 0.022). Conclusions: This study showed strong correlation between dental age, chronological age, and salivary alkaline phosphatase; hence, estimation of dental age and salivary alkaline phosphatase in Indonesian children during early and late childhood has significant meaning to chronological age.